Digoxin reduces atherosclerosis in apolipoprotein E‐deficient mice. (11th March 2016) - Shi, Huairui; Mao, Xiaobo; Zhong, Yucheng; Liu, Yuzhou; Zhao, Xiaoqi; Yu, Kunwu; Zhu, Ruirui; Wei, Yuzhen; Zhu, Jianghao; Sun, Haitao; Mao, Yi; Zeng, Qiutang
Abstract : Background and Purpose: Numerous in vitro studies have suggested that digoxin suppresses inflammation and alters lipid metabolism. However, the effect of dioxin on atherosclerosis is poorly understood. The present study was conducted to determine whether digoxin affects the development of atherosclerosis in a murine model of atherosclerotic disease. Experimental Approach: Apolipoprotein E‐deficient mice maintained on a Western‐type diet were administered PBS (control), low‐dose digoxin (1 mg·kg −1 · day −1 ) or high‐dose digoxin (2 mg·kg −1 · day −1 ) via i.p. injection for 12 weeks. Key Results: Digoxin dose‐dependently reduced atherosclerotic lesion formation and plasma lipid levels (reductions of 41% in total cholesterol, 54% in triglycerides and 20% in low‐density lipoprotein cholesterol in the high‐dose digoxin‐treated group). Moreover, treatment with digoxin markedly attenuated IL‐17A expression and IL‐17A‐related inflammatory responses and increased the abundance of regulatory T cells (Tregs). Conclusions and Implications: Our data demonstrate that digoxin acts as a specific antagonist of retinoid‐related orphan receptor‐γ to decrease atherosclerosis by suppressing lipid levels and IL‐17A‐related inflammatory responses.